Interfacial scattering effect on anomalous Hall effect in Ni/Au multilayers. (16th May 2017) - Zhang, Qiang; Li, Peng; Wen, Yan; He, Xin; Zhao, Yuelei; Zhang, Junli; Zhang, Xixiang
Abstract: The effect of interfacial scattering on anomalous Hall effect (AHE) was studied in the ( Ni 36 n   nm / Au 12 n   nm ) n multilayers. Field-dependent Hall resistivity was measured in the temperature range of 5–300 K with the magnetic field up to 50 kOe. The anomalous Hall resistivity ( ρ AHE ) was enhanced by more than six times at 5 K from n   =  1 to n   =  12 due to the increased interfacial scattering, whereas the longitudinal resistivity ( ρ x x ) was increased nearly three times. A scaling relation ρ AHE ∼ ρ x x γ with γ = 1.85 was obtained for ρ AHE and ρ x x measured at 5 K, indicating that the dominant mechanism(s) of the AHE in these multilayers should be side-jump or/and intrinsic in nature. The new scaling relation ρ AHE = α ρ x x 0 + β ρ x x 0 2 + b ρ x x 2 (Tian et al 2009 Phys. Rev. Lett .103 087206) has been applied to our data to identify the origin of the AHE in this type of multilayer.